Clarity and Finality. About the Transcendental Conception of Human Identity - Moryń, Mariusz (Sensus Historiae, 2020)
Issues depicted in the article are of authorial character and refer to the connections amongst subjectivity, the work of hand and eschatology. The hand creates and unveils the absolute finality, which is understood as extreme evidence. Human identity is described through reference to transcendental human constitution, namely from the point of view of the clear subject. Therefore, the human becomes a form of constituting reality, in sense. The Author’s focus lies mainly on portraying an individual as a being unveiling transparency of the world. The human distinguishes, marks and changes the world as a result of these actions. Abovementioned topics are connected to living life in its solemnity, the life that is justified and grounded in destiny.